Influence of Fuel Temperature on a Diesel Engine Performance Operating with Biodiesel Blended - Rafidah, Rahim; R., Mamat; Mohd Yusof, Taib; Abdul Adam, Abdullah (Science & Engineering Research Support Society, 2012)
This paper is presented to study the effect of temperature using 5 % biodiesel blended on diesel engine performance. The one-dimensional numerical analysis of GT-Power software is used to simulate the commercial four cylinder diesel engine. The standard fuel data base of GT-Power does not contain any biodiesel. Therefore, the authors have measured typical physical properties of the fuel before it can be installed into the GT-Power data base. The diesel engine is simulated to study the characteristic of engine performance when the engine is operating with fuel blend as an alternative fuel. The simulations are conducted at full load condition where the temperature are varies from 300K to 500K. The simulation results show that the brake power and brake torque reduced maximum of 1.39 % and 1.13 % respectively for the engine operating with fuel blend at different temperatures. It was shown that the insignificant different is due to the small gap between energy content values. The decrease in the lower heating value caused an increase in the brake specific fuel consumption thus reduces the brake thermal efficiency of engine performance at full load.